Thermal degradation behavior of cellulose-based material for gating systems in iron casting production - Grabowska, B.; Szucki, M.; Suchy, J. S.; Eichholz, S.; Hodor, K. (Polimery, 2013)
This study presents a fragment of research aimed at determining the thermal stability of a cellulose-based composite material used for building gating systems for large iron castings. The behavior of the material itself at elevated temperatures is of major significance for the mould filling process. In this research, thermal analysis methods (DTG, TG, DSC) were used to explain the course of the thermal degradation of the analysed material by establishing thermal effects of transformations occurring during its heating as well as its structural and mass changes. The research was conducted at the temperature range of 40—1000 °C. The degradation process was found to start at the temperature of approx. 300 °C, and the total mass loss at the range of 300—750 °C amounted to 48.8 %. The mass loss observed is accompanied by very strong exothermal effects. The remaining part of the sample mass which had not decomposed up to the temperature of 1000 °C (approx. 51.2 %) probably represents the carbon fibres and ceramic clay present in the material, because these decompose at a temperature higher than the range of the performed thermal analysis and higher than the temperature of the liquid metal fed into the gating system (about 1300— 1400 °C). In addition, volatile products of degradation were analysed using IR spectrum and the thermogravimetry (TG) method coupled online with mass spectrometry (MS). In the temperature range 300—750 °C signals for small molecular masses were noticed, which indicates that the degradation process and fragmentation of polymer chains in the cellulose occur as well as formation of small particle compounds, primarily H2O and CO2. No signals given off by aromatic compounds were detected.